Licófitas e samambaias da Serra do Itauajuri, município de Monte Alegre, Pará, Brasil - GÓES, Julieta Pallos Pinto de Araújo (Instituto de Pesquisas Jardim Botânico do Rio de Janeiro, 2018)
In this study we present the lycophytes and ferns inventoried in the Serra do Itauajuri, Pará state. Sixty four species distributed in 36 genera and 21 families were registered, with one family, one genus, and four species belonging to the lycophytes lineage, and 20 families, 35 genera, and 60 species belonging to the ferns lineage. The most representative families were Pteridaceae (19 spp.), Polypodiaceae (8), and Selaginellaceae (4). The genera with highest species richness were Adiantum (9 spp.) and Selaginella (4). Most species were collected as terrestrial (35 spp., ca. 55%), occurring in riparian forests (51 spp., ca. 80%), with American distribution pattern (46 spp., ca. 72%). We present two new records for the Northern Region of Brazil (Asplenium pumilum and Marsilea ancylopoda) and two for Pará state (Ophioglossum nudicaule and Selaginella minima). The studied area has distinct environmental characteristics than those commonly observed in Brazilian Amazonia, being a biologically important area. This results gathered information that can support the creation and implementation of the Serra do Itauajuri Conservation Unit, which will guarantee the preservation of its historic and natural wealth.